2015
DOI: 10.1111/ddg.12729
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors associated with health‐related quality of life and psychological distress in vitiligo

Abstract: Our results indicate that the psychosocial adjustment to the disease is mainly influenced by subjective factors. This observation could imply the need for targeted support interventions in the treatment of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 24 publications
3
46
0
4
Order By: Relevance
“…Regardless of the etiology, the disease results in disfiguring, milky white patches or macules on the skin, most commonly on the hands and face. These lesions follow an inconsistent course, during which long periods of steady disease may be interrupted without a known trigger 5 …”
Section: Prevalence and Pathophysiologymentioning
confidence: 99%
“…Regardless of the etiology, the disease results in disfiguring, milky white patches or macules on the skin, most commonly on the hands and face. These lesions follow an inconsistent course, during which long periods of steady disease may be interrupted without a known trigger 5 …”
Section: Prevalence and Pathophysiologymentioning
confidence: 99%
“…Since the depigmented patches of vitiligo are highly visible and often unpredictable, the disease carries a high psychosocial burden for patients [2]. Examination of the psychosocial impact among patients with vitiligo has revealed increased risk of depression, anxiety, and social isolation as well as detrimental effects on body image and self-esteem [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study vitiligo affected work in 8 cases (9.3%) . Another study reported that disease severity and psychological fallout had not been found strongly associated [20].Vitiligo requires ongoing psychosocial support. There is a strong need for a psychoeducational intervention with focus on acceptance and managing social impact [21].…”
Section: Resultsmentioning
confidence: 99%